Revisiting the Consumer Protection Law in the digital-based business era: A Study of Trade Law - Manullang, Sardjana Orba; Maruf, Irma Rachmawati; Sembiring, Tamaulina Br; Purbaningsih, Yuli; Hendriarto, Prasetyono (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study discusses the review of consumer protection law in the era of internet-based trade. The author believes that along with technological advances, more and more business transactions are carried out electronically. So along with that, there are also business actions that harm consumers. For this reason, the author has conducted a search for scientific evidence to support the hypothesis of this study on a number of databases that discuss the issue in question. We then analyze the data to get a valid and convincing understanding. Based on the findings and discussion of the results, we can conclude that the consumer protection law needs to be strengthened with more binding rules while still taking into account the basic existing consumer protection laws, namely UUPK article 4 of electronic trading regulations.